Variation in caries and treatment experience in 35–44-year-old Lithuanians - Aleksejuniene J, Eriksen HM, Holst D (Blackwell Synergy, 2000)
Data summarising caries levels differ between countries and often conceal large variations. These differences may reflect variations at individual, group, social and other levels. Caries and treatment experience differences are found to be significantly related to a variety of clinical and non-clinical factors. Variation in caries within Lithuanian children has been reported and related to background-, behavior-, dental care- and other factors. Variation in general or related to any factors in adult Lithuanian population has not been studied.